Juridical Protection for Internship Participants Who Fail to Obtain Their Legal Rights - Khyatudin, Khyatudin; Haq, Rifqi Arroiqul Haq Arroiqul (UNISKA LAW REVIEW, 2025)
The apprenticeship program is a form of job training prepared for students or prospective workers in preparation for entering the world of work. Some of the rights of apprentices are not the same and must be distinguished from permanent workers in a company, this needs to be done to avoid exploitation and arbitrariness against apprentices. The purpose of this study is to analyze what types of legal protection can be obtained for apprentices when their rights cannot be fulfilled by the company, as well as to analyze the legal consequences that must be accounted for by companies that have been caught violating the rights of apprentices. In completing this research the author used normative research methods. The results of the research show that the regulations governing the rights of apprentices have been very clearly regulated in the applicable laws in Indonesia, namely in Law No. 13 of 2003 concerning Manpower and Minister of Manpower Regulation No. 6 of 2020 concerning the Implementation of Domestic Apprenticeship. However, in reality in the field, many apprentices and companies do not clearly understand and apply these regulations, which is what causes many cases of exploitation and arbitrariness against apprentices. One of the cases that is the source of the author's research is in Decision Number: 111/Pdt.Sus-PHI/2019/PN.JKT.PST. In addition to the rights of apprentices, the results of the study also show that companies must bear the legal and social impacts when they are found to be unable to fulfill and violate the rights of apprentices. The legal and social impacts include sanctions under applicable laws, cancellation of the apprenticeship agreement letter, threat to the company's reputation and prohibition to participate in apprenticeship programs held by the government.